2022
DOI: 10.1038/s41598-022-15297-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of bioactive peptides from a Brazilian kefir sample, and their anti-Alzheimer potential in Drosophila melanogaster

Abstract: Alzheimer’s disease (AD) is the most common form of dementia in the elderly, affecting cognitive, intellectual, and motor functions. Different hypotheses explain AD’s mechanism, such as the amyloidogenic hypothesis. Moreover, this disease is multifactorial, and several studies have shown that gut dysbiosis and oxidative stress influence its pathogenesis. Knowing that kefir is a probiotic used in therapies to restore dysbiosis and that the bioactive peptides present in it have antioxidant properties, we explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…A previous work reported the FTIR spectra of AChE with similar result of 35% α-helical and 16% β-sheet fractions (38). AChE has high conformational flexibility due to its spatial arrangement of a pair of four helical structures placed in an antiparallel fashion leaving a large space at the center (15). As a result, the enzyme has increased solvation in aqueous environments, which could be the explanation for the slightly unfolded structure of AChE as observed with the fluorescence spectra (38).…”
Section: Circular Dichroic Spectra Of Acetylcholinesterase and Effect...mentioning
confidence: 63%
See 3 more Smart Citations
“…A previous work reported the FTIR spectra of AChE with similar result of 35% α-helical and 16% β-sheet fractions (38). AChE has high conformational flexibility due to its spatial arrangement of a pair of four helical structures placed in an antiparallel fashion leaving a large space at the center (15). As a result, the enzyme has increased solvation in aqueous environments, which could be the explanation for the slightly unfolded structure of AChE as observed with the fluorescence spectra (38).…”
Section: Circular Dichroic Spectra Of Acetylcholinesterase and Effect...mentioning
confidence: 63%
“…However, the structure of the enzyme became more compact after interaction with LQHNA, and a higher intensity occurred with the Phe residue at 3.13 µg/ml peptide concentration. A study carried out by Fale et al (15) to determine the interaction between Plectranthus barbatus herbal tea components and AChE showed that only Trp residues contributed to the fluorescence emission of the enzyme. The study also showed that there was no shift in the position of the Trp residues, which means that although the inhibitor interacted very closely with AChE to quench fluorescence, the secondary and tertiary structures of the enzyme may not have been altered (15).…”
Section: Intrinsic Fluorescence Spectra Of Acetylcholinesterase and F...mentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, the exopolysaccharides produced by kefir specific microorganisms have been shown to have anti-obesity and immunomodulatory activity ( Vinderola et al, 2006a ; Lim et al, 2017 ), while cell-free fractions of kefir have also been shown to have immunomodulatory, lipid lowering, and anti-cancer effects ( Vinderola et al, 2006b ; Gao et al, 2013 ; Santanna et al, 2017 ). Additionally, kefir peptides and peptide fractions have been shown to have a wide range of health impacts including reductions in hyperlipidemia, atherosclerosis, improved neurological function, and reduced non-alcoholic fatty liver disease (NAFLD) risk ( Quiros et al, 2005 ; Chen et al, 2016 ; Tung et al, 2017 , 2020 ; Malta et al, 2022 ). There is also some evidence that kefir or kefir components may improve factors associated with atherosclerosis and cardiovascular disease (CVD) development, both of which are associated with obesity and hyperlipidemia ( Santanna et al, 2017 ; Tung et al, 2020 ; Ghizi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%